2012
DOI: 10.5380/rf.v42i1.26297
|View full text |Cite
|
Sign up to set email alerts
|

AVALIAÇÃO DE DIFERENTES NÍVEIS DE DESBASTE NAS PROPRIEDADES DA MADEIRA E DO CARVÃO VEGETAL DE Eucalyptus grandis x Eucalyptus urophylla

Abstract: ResumoO presente trabalho teve como objetivo avaliar os efeitos de diferentes níveis de desbaste nas propriedades físicas e químicas da madeira e do carvão vegetal de híbrido de Eucalyptus urophylla W. Hill ex Maiden x Eucalyptus grandis S. T. Blake. O experimento foi instalado em um talhão de uma empresa do setor florestal, que foi dividido em quatro faixas, representando os níveis de desbaste de 0, 20, 35 e 50% aplicados ao povoamento aos cinco anos. Foram coletadas 3 árvores de cada tratamento, 62 meses pós… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 3 publications
4
12
0
13
Order By: Relevance
“…The charcoal produced at the final temperature of 750 °C presented smaller amounts of volatile matters ( Figure 2E), due to their higher disposal at higher temperatures. Thus, one can notice higher fixed carbon content occurred in these charcoal samples ( Figure 2F) caused by the increase of the final temperature of carbonization, already well known in the literature (WENZEL 1970;VALENTE et al, 1985DERMIRBAS, 2004OLIVEIRA et al, 2010).…”
Section: Gravimetric Yields and Charcoal Analysissupporting
confidence: 71%
See 1 more Smart Citation
“…The charcoal produced at the final temperature of 750 °C presented smaller amounts of volatile matters ( Figure 2E), due to their higher disposal at higher temperatures. Thus, one can notice higher fixed carbon content occurred in these charcoal samples ( Figure 2F) caused by the increase of the final temperature of carbonization, already well known in the literature (WENZEL 1970;VALENTE et al, 1985DERMIRBAS, 2004OLIVEIRA et al, 2010).…”
Section: Gravimetric Yields and Charcoal Analysissupporting
confidence: 71%
“…Therefore, the way the carbonization is driven interferes actively on the final quality of charcoal, such as density, strength, moisture content, fixed carbon content, ash content and volatile matters (OLIVEIRA et al, 2010;DIAS JÚNIOR et al, 2015a). According to Trugilho and Silva (2001), the final carbonization temperature is one of the variables most related to the final quality of charcoal.…”
Section: Introductionmentioning
confidence: 99%
“…In the immediate chemical analysis of charcoal, Oliveira et al (2010), Oliveira et al (2012) and Santos et al (2011) reported VM rates ranging between 9.71 and 26.43%, As rates between 0.39 and 2.60% and FC rates between 73.05 and 88.17%. A significant statistical difference is noticed between the average volatiles matter of the treatments.…”
Section: Discussionmentioning
confidence: 98%
“…Um problema relacionado à utilização do carvão vegetal é sua alta variabilidade em qualidade, uma vez que esse produto sofre grande influência da madeira que lhe deu origem e do sistema de produção. Essa variabilidade ocasiona grande desperdício do material, pois dificulta a operação dos alto-fornos siderúrgicos (OLIVEIRA et al, 2010).…”
Section: Introductionunclassified
“…Um problema relacionado à utilização do carvão vegetal é sua alta variabilidade em qualidade, uma vez que esse produto sofre grande influência da madeira que lhe deu origem e do sistema de produção. Essa variabilidade ocasiona grande desperdício do material, pois dificulta a operação dos alto-fornos siderúrgicos (OLIVEIRA et al, 2010).A qualidade do carvão vegetal utilizado na siderurgia influencia na qualidade do produto final. A qualidade e a quantidade do carvão vegetal produzido dependem basicamente de características físico-químicas da madeira e do processo de produção.…”
unclassified